4-(4-Pyridyl)pyridinium 3-amino-5-carboxy-2,4,6-triiodobenzoate-5-amino-2,4,6-triiodoisophthalic acid (1/1) - Zhang, Kou-Lin; Diao, Guo-Wang; Ng, S.W. (International Union of Crystallography, 2010)
In the title ammonium carboxylate-carboxylic acid co-cystal, C10H9N2+center dot C8H3I3NO4-center dot C8H4I3NO4, the carboxylate anion and carboxylic acid molecule are linked by O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds to form a chain running along the c axis of the monoclinic unit cell. The chains are linked by pyridinum and pyridine N-H center dot center dot center dot O hydrogen bonds, generating a layer motif. O-H center dot center dot center dot N and O-H center dot center dot center dot O hydrogen bonds are also observed.